Sistem Deteksi dan Pencatatan Akses Perpustakaan Menggunakan Sensor Gerak IoT dengan Visualisasi Data Berbasis Website - Febriyanti Panjaitan; Jehuda Rapha Putra Hermantan; Leon Duta Effendy; Frederick Kinton (Universitas Multi Data Palembang, 2026)
This study aims to develop a prototype of an Internet of Things (IoT)–based people counting system for real-time room occupancy monitoring. The scope of the research is limited to the design and implementation of a physical prototype and data visualization through a web dashboard, without involving individual identification. The research employs an experimental and system development (Research and Development) method using infrared sensors, Arduino Uno, ESP32, and a servo motor. The system is designed to detect entry and exit activities, count the number of people, and transmit data to a server via a Wi-Fi network to be displayed on a web dashboard. The results show that the system operates as designed, performing automatic counting and presenting real-time occupancy information. In conclusion, the developed IoT system can serve as an initial solution for room occupancy monitoring and has the potential to be further developed through the integration of face recognition technology